Targets and Scope in Modified Sub - Radical Mastectomy - Armand Ugon, Alfredo; Cassinelli, Daniel; Sáez, Hugo (Cirugía del Uruguay, 1981)
Evaluation of 39 patients suffering from Grade I y II breast cancer treated by Merola's operation, confirms validity of this mastectomy which involves the right extent of radicality, is well tollerated, has low merbility and sequella, presents advantages vis - á - vis the Meyer - Halstead having neither the indications nos the importance of complete axillary évidement.